A theoretical alternative intraosseous infusion site in severely hypovolemic children - Nkhensani Mogale; Albert-Neels van Schoor; Marius C. Bosman (AOSIS, 2015)
Background: Studies have shown that the venous system tends to collapse during hypovolemic shock. The use of the bone marrow space for infusions is an effective alternative, with the tibial insertion site being the norm. Objectives: This study was conducted to determine a quick intraosseous infusion method that could be an alternative to the tibial route in neonates during emergency situations. Method: A sample of 30 neonatal cadavers was dissected to explore a possible alternative to the tibial insertion site. The needle was inserted in the superolateral aspect of the humerus. The needle infusion site was then dissected to determine possible muscular and neurovascular damage that might occur during the administration of this procedure, with the greatest concern being the posterior circumflex humeral artery and axillary nerve exiting the quadrangular space. The distance of the needle insertion site was measured in relation to the soft tissue aswell as to bony landmarks. Results: The calculated 95% confidence interval shows that the needle can be safely inserted into the intraosseous tissue at the greater tubercle of the humerus 9.5 mm - 11.1 mm from the acromion. This is about a little finger's width from the acromioclavicular joint. Conclusion: Anatomically, the described site is suggested to offer a safe alternative access point for emergency infusion in severely hypovolemic newborns and infants, without the risk of damage to any anatomical structures.